Uphill walking and running: strategies to improve performance - Giovanelli, N. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
Trail running (mountain running) races include uphill and downhill sections that requires continuous adaptations in walking/running mechanics and energetics. Among other factors (such as maximal oxygen uptake (VO2max) and fraction of VO2max (F)), the cost or transport (CoT) is one of the most important in determining the endurance performance (Lazzer et al. 2012). In particular, to optimize the performance athletes should increase their VO2max and/or F or to decrease their CoT. Thus, adopting specific strategies to improve CoT leads to a better performance (Hoogkamer et al. 2016). One of the most important aspect that affect the CoT is the power of the lower limbs (Lazzer et al. 2014). In turn, this is related to a lower increase of CoT during uphill marathon and an increase in power of the lower limbs leads to a lower CoT in endurance athletes. Different training strategies may be used for obtaining an increase in power, such as adding plyometric and explosive exercise to the normal training plan (Giovanelli et al. 2017; Spurrs et al. 2003). (Barnes and Kilding 2015) suggested some strategies for improving the CoT in runners but for trail runners it is important to adopt specific methods. Recent studies suggested some strategies to optimize the CoT during uphill locomotion. In particular it is suggested that walking is cheaper than running above a certain incline and below a certain speed (Giovanelli et al. 2016; Ortiz et al. 2017). Also, the use of poles, which increases the CoT during level walking (Pellegrini et al. 2015) seems to decrease the CoT during steep uphill walking (Giovanelli et al. 2019). In conclusion, there are specific strategies to be adopted during training sessions and competitions that leads to a lower CoT, allowing athletes to achieve a better performance.